Assessment of genetic purity of cotton cultivars (Gossypium hirsutum L.) using morphological characteristics and microsatellite marker (SSR) - maryam najafian; Ghasem tohidloo; A. Hamidi; farzad paknejad; mehdi rezaei (علوم و فناوری بذر ایران)
In order to evaluate the genetic purity and originality of three common commercial cotton cultivars (Varamin, Khordad and Bakhtegan) using morphological characteristics and microsatellite markers, the seeds of these cultivars along with pure lines in the field in a two-year randomized complete block design with four replications two methods of field growth test (GOT) and microsatellite markers were tested. The results of the GOT test showed that the pure samples of the cultivars were different from the off-type and non-pure samples in 7 morphological characteristics, and these traits, which are not influenced by the environment, can be used as a key to identify the desired cultivar. In the molecular test, out of 7 markers, 3 pairs were selected due to their resolution and the number of effective alleles (DPL431, DPL0513, and CIR246). Due to the similarity of the results of GOT methods and microsatellite markers and due to the high cost of the molecular method, this method can be used as a quick, case-by-case and complementary method to determine the genetic purity percentage of cultivars.